The Effect of School Operational Assistance Program on Investment in Education by Households: Evidence from Indonesia - Nia Pramita Sari; Ryuichi Tanaka (Institute for Economic and Social Research, 2019)
The School Operational Assistance Program, referred to as BOS, is a demand intervention program indirectly provided by the government of Indonesia to students through schools, started in July 2005. This paper examines the impact of BOS on educational investment by households and other expenditure such as food and non-food consumption. Using the observations of 1,161 households with at least one member studying in public school from the fourth wave of the Indonesian Family Life Survey (IFLS 4), we discover that BOS is effective in relaxing household’s budget constraint, thus increasing educational investment by households. We also discover that households with low income benefit significantly from BOS relative to those with high income. Additionally, we discover that BOS assists households, regardless of their income level, in increasing their spending on food and non-food items.